Thorpe–Ingold Effect in Branch‐Selective Alkylation of Unactivated Aryl Fluorides. Issue 29 (19th June 2018) - O'Neill, Matthew J.; Riesebeck, Tim; Cornella, Josep
Abstract: Presented herein is a general protocol for the alkylation of simple aryl fluorides with unbiased secondary Grignard reagents by means of nickel catalysis. This study revealed a general Thorpe–Ingold effect in the ligand backbone which confers a high degree of selectivity for the secondary carbon center in the C−C coupling event. This protocol is characterized by mild reaction conditions, robustness, and simplicity. Both electron‐rich and electron‐deficient aryl fluorides are suitable candidates in this transformation. Equally amenable are a variety of heterocycles, permitting the coupling without over alkylation at the electrophilic sites. Abstract : Crossing over : Cross‐coupling of aromatic C−F bonds with secondary alkylmagnesium nucleophiles has been accomplished by means of nickel catalysis. gem ‐Dialkyl substitution of the ligand backbone, producing a Thorpe–Ingold effect, resulted in a chelation effect which translated into high yields and selectivities for retention of the nucleophile configuration.